Risk factors and subtypes of ischemic strokes in young adults: A tertiary care hospital study from southern part of India - Konda M; Varalakshmi EA; Patil A; Kaul S; Yada PK; Jayasree M; Sitajayalakshmi S; Surath M (Journal of Medical and Scientific Research)
Background: In the last few decades ischemic stroke in young adults (15-45 years) has been increasingly reported. This study was aimed to evaluate the epidemiological features, risk factors and mechanisms of ischemic stroke in young adults.